Synthesis and Theoretical Study of Amide Compounds Containing Aminothiophene and Six-Membered Heterocyclic Rings - Colak, Naki; Ilci, Elifhan; Basceken, Sinan; Muhammet, Sinan Mithat; Turan, Nevin; Buldurun, Kenan (Wiley-V C H Verlag Gmbh, 2025)
In our present study, the efficient pathway 6-member heterocyclic 2-amino thiophene derivatives titled 2-amino-5,5,7,7-tetramethyl-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carbonitrile, and methyl 2-amino-6-methyl-4,5,6,7-tetrahydrothieno[2,3-c]pyridine-3-carboxylate were synthesized using 3,3,5,5-tetramethylcyclohexanone and 1-methylpiperidine-4-one. These synthesized 2-aminothiophene compounds were interlocked with derivatives of nitro and chloro benzoyl chloride compounds. The structures of all the compounds were characterized used by FT-IR, 1H NMR, 13C APT NMR, and mass spectroscopic methods. Then theoretical studies of these synthesized amid compounds were carried out. Optimization of all compounds with density functional theory (DFT) calculations was performed by using the B3LYP hybrid functional method and 6-31+g(d,p) basis sets in the Gaussian09 program package. The transition states (TSs) were checked to have one negative frequency. From TSs, intrinsic reaction coordinate (IRC) calculations were conducted to obtain the reactants and products of the energy minima. All calculations were carried out in toluene as a solvent phase with a radius of 0.3 & Aring;.
Keywords: 1-Methylpiperidin-4-one; Aminothiophene; Density functional theory; Heterocyclic compounds; Spectroscopic methods